Workshop as an exercise of learning and collaborative listening: the case of the review of National Policy of Health Promotion - Guerra, Vanessa de Almeida; Rezende, Regiane; Rocha, Dais Gonçalves; Silva, Kleber Rangel; Akerman, Marco (ABCS Health Sciences, 2015)
Introduction: The objective of this paper is to present the report of Southeast Workshop as part of the review process of National Policy of Health Promotion (PNPS). Experience report: That used the documentary analysis of the reports of the workshops in the Southeast, reading articles and observation notes of the authors regarding the systematization workshops and consensus. A matrix of southeastern was built in order to strengthen the regional profile, when considering local realities coming from the world of work of the various actors involved in the southeastern region of workshops in their respective areas of practice and implementation of health promotion actions. The regional workshop enabled the democratic participation of local stakeholders sharing knowledge and practices. By identifying local actions for health promotion, list the issues to be worked through operating axes, and, in line with the principles and values, the workshop participants were able to systematize the directives that are close to the determinants and health conditions. Conclusion: The methodology developed in the workshop points to the possibility of replicating it in different dimensions, the state levels, municipal, district and local providing reflections to make alive the new PNPS.